Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T16:57:02+01:00
A) x-1 przez 2 =4,6+3½ / *2
x-1= 2*4,6 + 2 * ⁷/₂
x-1 = 9,2 + 7
x = 9,2+7+1
x = 17,2

b)7xprzez2+2xprzez3=11x+13⅔ / *6
3*7x + 2* 2x = 6 * 11x + 6 * ⁴¹/₃
21x+4x=66x+82
21x+4x-66x = 82
-41x = 82/ : (-41)
x = -2

c)x-5 przez 8 =5x-18 przez 12 / *48
12 * (x-5) = 8 * (5x-18)
12x -60 = 40x -144
12x-40x = -144+60
-28x = -84 / : (-28)
x = 3

d 4 przez x -2=15 przez 12 x-1⅓
4 (12x- ⁴/₃) = 15 (x-2)
48x - ¹⁶/₃ = 15x - 30
48x-15x = -30+ ¹⁶/₃
33x = -24⅔ / :33
x = -⁷⁴/₃ *¹/₃₃
x= -⁷⁴/₉₉